The influence of sleep quality and quantity on soccer injuries in professional teams - Yabroudi, M. A.; Nawasreh, Z. H.; Debes, W. A.; Al-Sharman, A. J.; Darwish, A. A.; Samaneh, H. A.; Bashaireh, K. M. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: There is inconsistency in the relationship between sleeping measures and the occurrence of soccer injuries. Further, most studies investigated sleeping quantity and quality during soccer season but not during off-season. The purpose of this study was to determine the influence of sleeping off-season and during soccer season on the occurrence of injuries in professional soccer players. It was hypothesized that lower sleeping hours and players` thought of inadequate sleeping quantity and quality during off-season and soccer season would associate with the occurrence of soccer injuries. METHODS: One-hundred and fifty-two professional soccer players (premier league and division I teams, age: 21.82±4.44, BMI: 22.21±2.74, sex: men [N.=91], women [N.=61]) answered questions related to their sleeping duration and whether that amount of sleep was enough prior to (off-season) and during soccer season. The sleep questions related to sleep quantity were derived from the Arabic Pittsburgh Sleep Quality Index. Players indicated also. Players indicated their injury profile, medical treatment, and time loss due to soccer injury. Sleeping measures were evaluated using univariate and multivariate logistic regression models to determine predictors of soccer injuries. RESULTS: Sixty-eight players (44.73%) were injured. Lower total sleeping time during off-season (OR:0.66, 95% CI:0.51-0.85, P=0.002), answering no on "did you regularly get enough sleep during off-season" (OR: 5.64, 95% CI: 2.58-12.27, P<0.001), and answering no on "do you think that your sleeping hours during off-season were enough" (OR:4.76, 95% CI: 1.98-11.46, P=0.001) associated significantly with soccer injuries (R2:38). CONCLUSIONS: Lower total sleeping time and not getting regularly enough sleeping time during off-season associated with more soccer injuries. This highlights the influence of sleeping quantity and quality off-season on the occurrence of soccer injuries among professional players.